Functional Status of Senior Citizens of a Metropolitan City in Morang - Koirala, P.; Shrestha, S.; Koirala, M. (Kathmandu University Medical Journal, 2022)
Background Functional abilities start to decelerate after the age of 70 and causes need for assistance to do their basic activities of daily living (BADL) as well as instrumental activities of daily living (IADL).Objective To find out the functional status of senior citizens of a Metropolitan city in Morang.Method A descriptive cross-sectional study was carried out at Biratnagar Metropolitan City among 254 senior citizens receiving old age allowance using cluster sampling technique. Data were collected through face to face interview and measuring height and weight by researcher herself for the period of four weeks. Basic activities of daily living and instrumental activities of daily living were assessed using Katz Index of Basic Activities of Daily Living and Lawton Instrumental Activities of Daily Living tool with some modifications. Chi square test was used to assess the association between variables.Result About 48.4% and 90.6% of senior citizens had dependency in Basic Activities of Daily Living and Lawton Instrumental Activities of Daily Living respectively. The most common dependency for Basic Activities of Daily Living and Instrumental Activities of Daily Living was control of urination and defecation (31.9%) and using telephones (75.2%) respectively. Basic activities of daily living was significantly associated with age (p=0.0017), sex (p=0.013), literacy status (p=0.001), years of smoking (p=0.0029), social participation (0.0029) and history of fall within 1 year (p=0.038). Likewise Instrumental Activities of Daily Living was significantly associated with age (p=0.03), sex (p=0.035), literacy status (p=0.002), exercise (p=0.033) and social participation (p= 0.001).Conclusion It is concluded that about half of the senior citizens are dependent in Basic Activities of Daily Living and almost all of them are dependent in Instrumental Activities of Daily Living. So senior citizen clubs/ groups are suggested to be strengthened which may be effective in promoting independence, extending an active and healthy ageing.